Koncepcja zrównoważonego rozwoju a idea stanu stacjonarnego gospodarki - Kośmicki, Eugeniusz (The ideas of sustainable development and stationary state of economics, 2007)
The idea of “sustainability” originally used in a forest economy has been only developed at the beginning of the XVIII century. The idea of sustainable development were again investigated much later, i.e. in the second half of the XX century. However, J.S. Mili developed the idea of “stationarystate” in the XIX century which involved the crucial principles of the present idea of sustainable development. The idea assumed constancy of capital and population stocks. H.E. Dały developed the idea of “steady-state economics” in the second half of the XX century which was based on a steady State of matter and energy flows between economy and naturę. The idea of sustainable deyelopment describes the steady State of economy and society, which covers the basie economy and socio-cultural goals without compromising natural environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 79-88